(untitled) (Journal of Enam Medical College, 2013)
Background: Among the several human species of malarial parasites, Plasmodium falciparum can cause severe infection and if left untreated, there may be fatal complications. Early diagnosis and prompt treatment have been proposed to reduce the morbidity and mortality from malaria. Objective: To assess the diagnostic efficacy of antigen detection by immunochromatographic test (ICT) at different levels of parasitemia for diagnosis of malaria. Materials and Methods: This study was carried out in the department of Microbiology, Mymensingh Medical College for a period of one year from July 2005 to June 2006. A total of 98 clinically suspected malaria patients were included in this study. Peripheral blood films (PBF) were examined under microscope and parasite count/?L of blood was performed. Subsequently ICT for malaria antigen was done for each case. Results: Out of 59 cases positive by microscopic examination of blood films, 54 cases had parasitemia >600 parasites/?L of blood and all these cases were positive by ICT for malaria antigen. Rest 5 cases showed parasitemia <600 parasites/?L of blood and one case was found positive by ICT for malaria antigen. Conclusion: Immunochromatographic test can be used for early diagnosis of malaria with hyperparasitemia, especially for cerebral malaria. Journal of Enam Medical College; Vol 3 No 2 July 2013; Page 88-90 DOI: http://dx.doi.org/10.3329/jemc.v3i2.16130